2016
DOI: 10.1155/2016/6804670
|View full text |Cite
|
Sign up to set email alerts
|

Migration of a Broken Kirschner Wire after Surgical Treatment of Acromioclavicular Joint Dislocation

Abstract: Kirschner wire (K-wire) is one of the commonly used implants in orthopaedics practice. Migration of the wire is one of the most frequently reported complications after fixation by the K-wire. In particular, it has been reported that a greater range of motion in the shoulder, negative intrathoracic pressure associated with respiration, gravitational force, and muscular activities may cause migration from the upper extremities. In general, thin and long foreign bodies with smooth surfaces that are localized with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 9 publications
0
15
0
4
Order By: Relevance
“…The migration of foreign bodies within the human body is a rare phenomenon. It has been reported that materials such as Kirshner or cerclage wire, which are frequently used in orthopedic surgeries, migrate to different regions from the areas where they are applied, such as the clavicle, patella or olecranon [1][2][3][4][5][6][7]. In some rare cases, bullets have been observed to migrate to different regions of the body following a gunshot injury [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The migration of foreign bodies within the human body is a rare phenomenon. It has been reported that materials such as Kirshner or cerclage wire, which are frequently used in orthopedic surgeries, migrate to different regions from the areas where they are applied, such as the clavicle, patella or olecranon [1][2][3][4][5][6][7]. In some rare cases, bullets have been observed to migrate to different regions of the body following a gunshot injury [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of surgical techniques have been reported to reestablish the anatomical acromioclavicular (AC) joint alignment. However, there is still no gold standard surgical approach [1][2][3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Early surgical procedures applying Kirchner wires or Steinman pins are no longer used due to the case reports of pin migration and the limitation of relative motion between the scapula and clavicle [2][3][4][5][6] . The hook plate through the acromion requires a secondary operation for implant removal and increases the risk of AC ligament injury 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Complications included vascular and nerve damage, tendon rupture, osteomyelitis, loss of fracture or dislocation reduction, superficial infection, and postoperative wire migration. 1 2 3…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism leading to migration is still unknown, although muscle activity is postulated as a possible cause. 2 3 4 5…”
Section: Introductionmentioning
confidence: 99%